Pro-Social Attitudes of The Young Generation Planning Their Own Business in The Time Of COVID-19 Pandemic – A Decision Tree Approach - Teresa MROCZEK; Adriana KASZUBA PERZ; Marta CZYZEWSKA (Communications of International Proceedings, 2021)
The pro-social behavior of entrepreneurs has been recognized and identified as an important part of the management processes of modern enterprises a long time ago. Currently their special role in the process of rebuilding economies because of the crisis caused by the COVID-19 pandemic is indicated. The pro-social attitudes of the young generation in the context of planning new businesses are an important challenge defined as a research problem in this article. It attempts to identify the profiles of potential entrepreneurs of the young generation by identification of factors encouraging and discouraging to start their own businesses, assessing their knowledge in the area, as well as attitudes towards social responsibility and willingness to implement social missions in their own businesses. The c4.5 method was used to build a decision tree in order to describe the profiles of potential entrepreneurs. The concept of decision trees enabled a more accurate identification of the most important factors and characteristics describing people who plan their own business in the future. Results show that the surveyed young people planning business present responsible social attitudes, although some of them admit that they are not guided by social missions when planning their own business. Getting independence, as well as the possibility of obtaining significant income and subsidies from the EU are important factors encouraging to business. The respondents have knowledge on CSR and some of them notice that by implementing their business in the form of a social enterprise, they could implement important social missions, reconciling them with economic goals.
Keywords: Business Intentions; Corporate Social Responsibility; Social Enterprise; Social Entrepreneurship